Selection of phytase producing yeast strains for improved mineral mobilization and dephytinization of chickpea flour - Pable, A.; Gujar, P.; Khire, Jayant Malhar (Journal of Food Biochemistry, 2014)
Among 600 yeast isolates screened for phytase production, five (Zygosaccharomyces bisporusNCIM 3265 and 3296, Williopsis saturnusNCIM 3298, Zygosaccharomyces priorionusNCIM 3299 and Schizosaccharomyces octosporusNCIM 3297) were selected as potential phytase producers. Phytase activity was found to be cell wall associated with temperature and pH optima of 50C and 4.0, respectively. Highest phytase production was attained in cane juice medium as compared with other media used. Addition of phytase to chickpea flour significantly enhanced mineral mobilization by approximately 20-28%, 26-37% and 24-42% for Zn2+, Fe2+ and Ca2+, respectively, and decreased phytic acid content by about 75-88%.